Low Latency Internet and Economic Growth: A Simultaneous Approach - Jochen Lüdering (International Telecommunications Society (ITS), 2016)
Given the quality of the available data on Internet access across several countries, it is necessary to evaluate alternative measures to assess the effect of Internet access on economic outcomes. The research at hand builds up on an earlier paper, which introduced a novel measure of Internet quality. A logical consequence has been to introduce the new indicator (average latency for a country) into established models of economic growth. The data used in this analysis spans the period from 2008 to 2014 and covers 155 countries. The findings largely confirm previous results, that Internet access is beneficial to economic growth and emphasize the appropriateness of technical measures of Internet quality for economic analysis. Apart from providing insight into the quality dimension these measures do not rely on survey data, but can be obtained directly requiring only a low level of investment, making the data collection process viable even for smaller institutions.
Keywords: O47; O57; L96; 330; Economic Growth; Simultaneous Equations; Internet; Latency